Pelatihan Tata Kelola Keuangan Bagi Anggota Kelompok Usaha Petani Ikan Di Koya Timur - Syaikhul Falah; Nurul Sakinah (The Community Engagement Journal, 2022)
The purpose of this community service activities is a part of developing Small and Medium Enterprises (SMEs). Important factor that the entrepreneurs should know is about bookkeeping. Simple bookkeeping for small and medium-sized businesses is quite important for their own business progress. One of the reason is the bad system that SMEs have. It cause the lack of government attention, and there are still many SMEs who are reluctant to think about complicated things such as accounting and financial management issues. They only think that it is enough to make a profit, then their business or SMEs that they have can run and developing. Based on the results of observations and interviews with the Fish Farmer Group in Koya Timur, it can be conclude that financial management is very important for business actors or other entrepreneurs, but there are still many obstacles faced in the implementation. One of them is the lack of partners concern to learn individually how to prepare financial reports properly. It is caused the low quality of human resources from SMEs actors in managing their own business finances which results in not developing the business owned by the business owner.